Analisis Faktor Internal Dan Eksternal Self-Efficacy Mengajar Mahasiswa Pendidikan Pada Mata Kuliah Praktik Keterampilan Mengajar - Syifa Aulia Zahra; Budiaman Budiaman; Martini Martini (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
Self-efficacy is an individual’s confidence about performed accompanied task by the ability to complete the work that has been given. PKM can improve confidence education student to teaching in providing direct learning to learners. The purpose of this study was to determine the factors that can increase self-efficacy of teaching in PKM courses. This research used a descriptive method with the research subjects of UNJ Social Studies Education Students class of 2020 who has attended the PKM course. UNJ Social Studies Education students have a moderate level of self-efficacy, which means that UNJ Social Studies Education students have the confidence to teach and are able to complete the task given during PKM. However, in the preparation process its implementation still has some shortage so that it can affect the self-efficacy of teaching. Influencing factors are (1) interest in becoming a teacher, (2) supporting courses, (3) implementation mechanisms, (4) sources of self-efficacy, Mastery Experience, Vicarious Experience, Social Persuasion, Physiological and Emotional State. Researchers can then use questionnaires so that the results obtained have definite numerical data so that self-efficacy can be measured properly.